Epigenetic events involved in organic cation transporter 1‐dependent impaired response of hepatocellular carcinoma to sorafenib. (11th February 2019) - Al‐Abdulla, Ruba; Lozano, Elisa; Macias, Rocio I R; Monte, Maria J; Briz, Oscar; O'Rourke, Colm J; Serrano, Maria A; Banales, Jesus M; Avila, Matias A; Martinez‐Chantar, Maria L; Geier, Andreas; Andersen, Jesper B; et al.
Abstract : Background and Purpose: The expression of the human organic cation transporter‐1 (hOCT1, gene SLC22A1 ) is reduced in hepatocellular carcinoma (HCC). The molecular bases of this reduction and its relationship with the poor response of HCC to sorafenib were investigated. Experimental Approach: HCC transcriptomes from 366 samples available at TCGA were analysed. Alternative splicing was determined by RT‐PCR. The role of miRNAs in SLC22A1 downregulation was investigated. Expression of Oct1 was measured in rodent HCC models (spontaneously generated in Fxr ‐/‐ mice and chemically‐induced in rats). hOCT1 was overexpressed in human hepatoma cells (HuH7 and HepG2). Sorafenib and regorafenib uptake was determined by HPLC‐MS/MS. Key Results: hOCT1 overexpression enhanced sorafenib, but not regorafenib, quinine‐inhibitable uptake by hepatoma cells. In rodent HCC, Oct1 was downregulated, which was accompanied by impaired sorafenib uptake. In mice with s.c.‐implanted HCC, sorafenib inhibited the growth of hOCT1 overexpressing tumours. In human HCC, hOCT1 expression was inversely correlated with SLC22A1 promoter methylation, whereas demethylation with decitabine enhanced hOCT1 expression in hepatoma cells. Increased proportion of aberrant hOCT1 mRNA variants was found in HCC samples. In silico analysis identified six miRNAs as candidates to target hOCT1 mRNA. When overexpressed in HepG2 cells a significant hOCT1 mRNA decay was induced by hsa‐miR‐330 and hsa‐miR‐1468. Analysis of 39 paired tumour/adjacent samples from TCGA revealed that hsa‐mir‐330 was consistently upregulated in HCC. Conclusion and Implications: Impaired hOCT1 expression/function in HCC, in part due to epigenetic modifications, plays an important role in the poor pharmacological response of this cancer to sorafenib. Abstract :